A rare development of tumoral calcinosis of the ear auricle - Lee, Sam Yong (Arch Craniofac Surg, 2018)
Tumoral calcinosis is a condition characterized by deposition of calcium salts in the skin and sub- cutaneous tissue, commonly found around the joints. However, tumoral calcinosis of the auricle is extremely rare. We present the case of a 13-year-old boy with tumoral calcinosis of the helix of the ear auricle. A 13-year-old boy presented with a 10-year history of an enlarging mass on the left auricle. The mass was hard, non-tender, and non-compressible. The patient had no history of trauma. Complete surgical excision and pathological examination of the specimen was performed. The final diagnosis of the excised mass was tumoral calcinosis. After 9 months of follow-up, there were no signs of recurrence of the tumor and the patient was satisfied with the surgical results. Tumoral calcinosis of the auricle is extremely rare and may be misdiagnosed as other tumors. Pathological examination is essential for definitive diagnosis and complete surgical excision should be considered as the treatment of choice.